Revision of the subgenus Omophron (s.str.) Latreille, 1802 (Coleoptera: Carabidae: Omophron) of the Afrotropical region - Anichtchenko, Alexander; Valainis, Uldis (Zootaxa, 2023)
Species of the subgenus Omophron (s.str.) Latreille, 1802 occurring in the Afrotropical region are reviewed, with 19 species now recognized, including six species described as new: O. (s.str.) schuelei sp. n. (Zambia), O. (s.str.) secundum sp. n. (Burkina Faso, Senegal), O. (s.str.) mimeticum sp. n. (Namibia), O. (s.str.) muellerae sp. n. (Kenya, Tanzania), O. (s.str.) occultum sp. n. (RSA) and O. (s.str.) pallidum sp. n. (Mali). Omophron (s.str.) congoense Deleve, 1924 = O. (s.str.) capense congoense Deleve, 1924 stat. n. is downgraded as subspecies. Three new subspecies: O. (s.str.) capense pumilum ssp. n. (Angola, Namibia, Zambia), O. (s.str.) capense kmecoi ssp. n. (Namibia), and O. (s.str.) capense isolatum ssp. n. (Tanzania) are described. New synonymy, O. dominicense Chaudoir, 1868 syn. n. = O. (O.) capense Gory, 1833; O. (s.str.) dissimile Deleve, 1924 syn. n. = O. (s.str.) ghesquierei Deleve, 1924 syn. n. = O. (s.str.) severini Dupuis, 1911 is proposed. A key to the species, together with illustrations of their habitus and aedeagus, are provided. The distributional data provided include many new locality records.